STATUS AND TRENDS OF MONITORING INSECT POLLINATORS IN MANGO ECOSYSTEM IN SOUTHERN GHANA - Annoh, Charles. E.; A. Ewusie, Ebenezer.; A. Cobblah, Millicent.; Y. Osae, Michael.; A. Boateng, Bernard.; Kwapong, Peter. K.; Aidoo, Kwame.; Bosu, Paul. P. (IJRDO-Journal of Applied Science, 2017)
Several insects including the bees and other animals like bats are estimated to boost pollinationservices of 35% of the world’s food crops like mangoes, vegetables and medicinal plants.Researchers have shown declining trends of populations of some wild pollinators, particularlythe honey bee. This study was to determine insect diversity, abundance and monitor seasonaltrends of insect pollinators in the mango ecosystem of ten selected farms in the southern part ofGhana. In each farm, a radial transect of 10-meter diameter was constructed. Thirty small plasticpan traps were placed singly on 30 polyvinylchloride pipes fixed at 1-meter intervals. The pantraps filled with soapy water, were colored of ten cohorts of florescent blue, yellow and whiterespectively. Monitoring was conducted during the flowering periods of the minor and majormango seasons of 2012 and 2013. A total of 2364 insects were trapped; the most abundant weredipterans (1435) largely made up of house flies. The hymenopterans (504) consisted of 418 beesand 86 wasps respectively. Blue (2.85) and white (2.09) colored traps attracted bees more thanyellow (1.62) colored traps (p=0.89). The flies were most attracted to white traps (5.38) followedby yellow (4.35) and blue (3.61), the least (p=1.35). In farms close to natural vegetation beesdeclined from 3.00 per trap per week in 2012 major season through to 1.00 in 2013 major season.The declining trend of bees in this study underscores the need to manage and conserve wildpollinators for sustainable food productivity